Implementasi Pembelajaran Yoga dalam Meningkatkan Konsentrasi Belajar di Sekolah Dasar Negeri 1 Sumerta - I Ketut Gunarta (UHN IGB Sugriwa Denpasar, 2017)
The influence of modernization needs to be balanced with physical and spiritual health so that people can work, human beings can accept, recognize and direct themselves. Healthy living is the dream and goal of every person. No one in this world expects his life to be sick, because in a state of sickness a human body will find it difficult to achieve his purpose in life. Among teenagers often occur deviant behaviors that interfere with health itself is also disrupt in the activity in school and environment. The moral degradation experienced by the younger generation is very important to be given guidance from parents, educators, community and government. Yoga practice implies the sradha strengthening and devotion to God, which can form the character of a virtuous, emotionally and spiritually intelligent young generation who is able to counteract the negative effects of globalization, provide peace of mind, body health and foster a sense of compassion for others, which can reduce stress. Yoga is included in the universal doctrine therefore everyone should be able to control all of his actions, protect, regulate and discipline his mind so as not to deviate from the teachings of dharma.